Prostaglandin E2 receptor PTGER4-expressing macrophages promote intestinal epithelial barrier regeneration upon inflammation. Issue 12 (7th February 2021) - Na, Yi Rang; Jung, Daun; Stakenborg, Michelle; Jang, Hyeri; Gu, Gyo Jeong; Jeong, Mi Reu; Suh, Soo Youn; Kim, Hak Jae; Kwon, Yoon Hey; Sung, Tae Sik; Ryoo, Seung Bum; Park, Kyu Joo; et al.
Abstract : Objective: Dysfunctional resolution of intestinal inflammation and altered mucosal healing are essential features in the pathogenesis of inflammatory bowel disease (IBD). Intestinal macrophages are vital in the process of inflammation resolution, but the mechanisms underlying their mucosal healing capacity remain elusive. Design: We investigated the role of the prostaglandin E2 (PGE2 ) receptor PTGER4 on the differentiation of intestinal macrophages in patients with IBD and mouse models of intestinal inflammation. We studied mucosal healing and intestinal epithelial barrier regeneration in Csf1r-iCre Ptger4 fl/fl mice during dextran sulfate sodium (DSS)-induced colitis. The effect of PTGER4 + macrophage secreted molecules was investigated on epithelial organoid differentiation. Results: Here, we describe a subset of PTGER4-expressing intestinal macrophages with mucosal healing properties both in humans and mice. Csf1r-iCre Ptger4 fl/fl mice showed defective mucosal healing and epithelial barrier regeneration in a model of DSS colitis. Mechanistically, an increased mucosal level of PGE2 triggers chemokine (C-X-C motif) ligand 1 (CXCL1) secretion in monocyte-derived PTGER4 + macrophages via mitogen-activated protein kinases (MAPKs). CXCL1 drives epithelial cell differentiation and proliferation from regenerating crypts during colitis. Specific therapeutic targeting of macrophages with liposomes loaded with an MAPK agonist augmented the production of CXCL1 in vivo in conditional macrophage PTGER4-deficient mice, restoring their defective epithelial regeneration and favouring mucosal healing. Conclusion: PTGER4 + intestinal macrophages are essential for supporting the intestinal stem cell niche and regeneration of the injured epithelium. Our results pave the way for the development of a new class of therapeutic targets to promote macrophage healing functions and favour remission in patients with IBD.